Depression with Comorbid Diabetes: What Evidence Exists for Treatments Using Traditional Chinese Medicine and Natural Products? - Lu, Yanting; An, Tao; Tian, Hu; Gao, Xueqin; Wang, Furong; Wang, Shijun; Ma, Ke (Frontiers in Pharmacology, 2021)
The comorbidity between diabetes mellitus (DM) and depression, two chronic and devastating diseases spreading worldwide, has been confirmed by a large considerable body of epidemiological and clinical studies. Due to the bi-directional relationship, the combination of DM and depression leads to poorer outcome in both conditions. Given the adverse effects and limited effectiveness of existing therapy for depression associated with diabetes, the development of novel therapeutic drugs with more potency and less side effects are still the most important goal. Following this idea, many researchers have made great efforts to investigate the potential of traditional Chinese medicine (TCM) and natural products including natural extracts and purified compounds in the treatment of comorbid diabetic depression. Here, we reviewed the related literatures, sorted out TCM and natural products that can remedy the comorbidity of diabetes and depression, and presented them on the basis of their mechanism of action, which mainly focused on shared risk factors including insulin resistance, oxidative stress and inflammation, and nervous disturbances. In short, this review suggested that TCM and natural products could broaden therapeutic alternatives to ameliorate the nasty association of DM with depressive disorders.